The Effect of Dihydromyricetin, a Natural Flavonoid, on Morphine-induced Conditioned Place Preference and Physical Dependence in Mice - Etemad, Leila; Farkhari, Hadi; Alavi, Mohaddeseh Sadat; Roohbakhsh, Ali (Drug Research, 2020)
Objective Dihydromyricetin (DHM), a natural flavonoid, is used to reduce alcohol hangover. It has a modulatory role on GABAA receptors with significant effects on seizure and anxiety in animal models. We aimed to evaluate the effect of DHM on morphine conditioned place preference (CPP) and withdrawal sings following morphine dependence using animal models.Methods The effect of DHM (1, 2 and 5 mg/kg, intraperitoneal; ip) on the acquisition and expression of morphine-induced CPP was evaluated in male mice. Administration of morphine for three consecutive days induced physical dependence. The withdrawal signs such as jumping and defecation were precipitated by administration of naloxone (8 mg/kg, ip). The effect of DHM on the development of physical dependence was assessed by injection of DHM before morphine administrations.Results DHM, at the dose of 5 mg/kg, reduced expression of morphine CPP with an increase in the locomotor activity. DHM, at the doses of 2 and 5 mg/kg, also reduced development of morphine CPP. DHM alleviated development of morphine-induced physical dependence at the dose of 1, 2, and 5 mg/kg by decreasing jumping and defecation.Conclusion These results indicated that DHM decreased acquisition and expression of morphine CPP and inhibited development of morphine-induced physical dependence.
Keywords: drug dependence; analgesic drugs; behavioural pharmacology; drugs of abuse